Resistência feminina e feminismo africano em Without a Name de Yvonne Vera - Silva, Sheila Dias da (2014)
Yvonne Vera is one of Africa’s most outstanding novelists in the international scene of the English language literature. Fiction is the vehicle used by her to articulate female experience repressed and silenced in her country. Vera portrays Zimbabwean society through women’s perspective, usually employing female narrators to tell her female characters’ stories. Vera’s writing arises from the need to reverse the structures of oppression and colonial stereotypes imposed on black women, reinforcing her role as a writer with feminist ideals. In Without a name (1994), the novel that is analyzed in this study, Vera brings the story of Mazvita, a woman who resists many types of violence, such as rape. Mazvita tries to overcome the trauma and seek a better future for her, but it is possible to realize the impossibility of hope in a world full of desolation caused by the war of liberation and African patriarchal oppression. The objective of this paper is to analyze the construction of female resistance in the novel through the investigation of the character’s body fragmentation. Some relationships between her possibilities of agency and reaction and the broken state of her body are also established in the current analysis. Similarly her connections with the social body of her community, as well as the ways in which African feminism is portrayed in this novel, also come under scrutiny. At the end of the analysis, it is possible to imply that Vera elaborates a narrative of annihilation in this novel, depicting the character’s attempts of resistance and overcoming as ruined in parallel with the weakening of her body and the hopelessness of her setting.